2018
DOI: 10.3390/ma11101824
|View full text |Cite
|
Sign up to set email alerts
|

Yb2O3 Doped Zr0.92Y0.08O2-α(8YSZ) and Its Composite Electrolyte for Intermediate Temperature Solid Oxide Fuel Cells

Abstract: Yb3+ and Y3+ double doped ZrO2 (8YSZ+4Yb2O3) samples were synthesized by a solid state reaction method. Moreover, 8YSZ+4Yb2O3-NaCl/KCl composites were also successfully produced at different temperatures. The 8YSZ+4Yb2O3, 8YSZ+4Yb2O3-NaCl/KCl (800 °C), and 8YSZ+4Yb2O3-NaCl/KCl (1000 °C) samples were characterized by x–ray diffraction (XRD) and scanning electron microscopy (SEM). The results showed that a dense composite electrolyte was formed at a low temperature of 800 °C. The maximum conductivities of 4.7 × … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…However, the current commercialization process of SOFC is still restricted by its excessively high operating temperature, as the ionic transport in electrolytes and the catalytic activity of cathode that are linked to the power output and lifetime of fuel cells are thermally driven processes. For instance, the most frequently used electrolyte by far, Y 2 O 3 -stabilized ZrO 2 (YSZ) strictly requires high temperature over 700 °C to reach a sufficient ionic conductivity to run the fuel cell [ 2 , 3 , 4 ]. For addressing this challenge, extensive efforts have been made to reduce the operating temperature of SOFCs to a lower range of 400–600 °C [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the current commercialization process of SOFC is still restricted by its excessively high operating temperature, as the ionic transport in electrolytes and the catalytic activity of cathode that are linked to the power output and lifetime of fuel cells are thermally driven processes. For instance, the most frequently used electrolyte by far, Y 2 O 3 -stabilized ZrO 2 (YSZ) strictly requires high temperature over 700 °C to reach a sufficient ionic conductivity to run the fuel cell [ 2 , 3 , 4 ]. For addressing this challenge, extensive efforts have been made to reduce the operating temperature of SOFCs to a lower range of 400–600 °C [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of SOFCs operating temperature is strongly required for efficient long-term operations and this reduction can be fulfilled by using a new class of ceramic electrolytes (i.e., ceria-based) as substitute of the commonly used Y 2 O 3 -doped ZrO 2 (YSZ) [ 5 ]. Furthermore, the powder precursors of these materials should be produced through a simple and cheap process, easily scalable at industrial level and characterized by a very high yield, thus making IT-SOFCs commercial exploitation actually real [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ionic conductivity of alumina-doped ScSZ was slightly lower than the pure one (2.6 × 10 −1 S•cm −1 at 1000 • C for pure ScSZ). Cui et al [143] reported a zirconia-based electrolyte with improved electrochemical efficiency by co-doping YSZ with ytterbia and preparing 8YSZ-4Yb 2 O 3 and 8YSZ-4Yb 2 O 3 -NaCl/KCl composites. Co-doping zirconia with higher valance cations like Y 3+ and Yb 3+ is a basic route that could increase the oxygen vacancy concentration in the resulting composites.…”
Section: Intermediate-temperature Electrolytesmentioning
confidence: 99%